Characteristic Features of the Transcriptome in a Rat Strain with Audiogenic Epilepsy - Chuvakova, Lyubov N.; Funikov, Sergey Yu.; Davletshin, Artem I.; Fedotova, Irina B.; Evgen’ev, Mikhail B.; Poletaeva, Inga I.; Garbuz, David G. (KnE Life Sciences, 2022)
Audiogenic epilepsy (AE), developing in rodent strains in response to sound, is widely used as the model of generalized convulsive epilepsy, while the molecular mechanisms determining AE are currently poorly understood. The brain region that is crucial for AE development isthe inferior and superior colliculi (IC, SC). We compared IC-SC gene expression profiles in rats with different AE susceptibility using transcriptome analysis.The transcriptomes were obtained from the IC-SC of Wistar rats (with no AE), Krushinsky-Molodkina (KM) strain rats (100% AE susceptible), and ”0” strain rats (with no AE) selected from F2 KM x Wistar hybrids for AE absence. KM gene expression displayed characteristic differences inboth of the strains that were not susceptible to AE. There was increased expression of a number of genes responsible for positive regulation of the MAPK signaling cascade, as well as of genes responsible for the production of interferon and several other cytokines. An increase in the expression levels of theTTR gene was found in KM rats, as well as significantly lower expression of the Msh3 gene (involved in post-replicative DNA repair systems). AE was also describedin the 101/HY mouse strain with a mutation in the locus controlling DNA repair. The DNA repair system defects could be the primary factor leading to the accumulation of mutations, which, in turn, promote AE. Keywords: udiogenic seizure, KM strain, transcriptome, TTR gene, Msh3 gene, DNA repair